Clinical recommendations for antibacterial therapy of community-acquired infections: what should a practitioner pay attention to? - I. V. Кovaleva (Лечащий Врач)
Results. The seminar featured presentations by Corresponding Member of the Russian Academy of Sciences, Rector of the Smolensk State Medical University, Chief freelance Specialist of the Ministry of Health of Russia on Clinical Microbiology and antimicrobial ResistanceS. Kozlov; Vice Director for Scientific Work of the Scientific Research Institute of Antimicrobial Therapy of Smolensk University, Candidate of Medical Sciences A. V. Dehnich; Associate Professor of the Department Phthisiopulmonology of Kazan State Medical University, Doctor of Medical Sciences I. Yu. Wiesel. Antibiotic resistance is one of the most serious global threats to human health, making it difficult to treat life-threatening infections. According to the forecast of the World Health Organization, the level of antibiotic resistance in the world may increase by 17% by 2050. This problem is extremely acute in cities with millions of inhabitants, which is associated with high population density, active migration processes, the growth of a stratum of unvaccinated people, outbreaks of ornithosis spread by pigeons, whose population is growing uncontrollably in megacities. The global situation of antibiotic resistance has only worsened since the COVID-19 pandemic. Conclusion. The increasing antibiotic resistance inside the population of cities with millions of inhabitants, especially after the COVID-19 pandemic, and the high risk of atypical (intracellular) infections characterized by bilateral damage of the nasopharynx in combination with damage of the lower respiratory tract, therapists should be informed about a rational choice of an effective antibacterial drug from the macrolide group that blocks not one or two, but three domains on the ribosome of the pathogen at once, exerting a triple bactericidal effect (spiramycin). Since this macrolide has avoided widespread use during the COVID-19 pandemic, infectious agents have not yet developed widespread resistance to it.